The Relationship between Serum Brain - Derived Neurotrophic Factor (BDNF) Level and Cognitive Function in Middle Aged Male Chronic Smokers - Han, Myitzu; Thwin, Mya Mya; Aung, Cho Lwin; Yi, Myat San; Yee, Khin Than; Mohd Nasir, Mat Nor; Bhagat, Vidya (RJPT, 2020)
Cigarette smoking is a pervasive high-risk behavior and recent studies reported that nicotine in tobacco influences a wide variety of cognitive domains. BDNF is one of the factors of the neurotrophin family that can regulate the cognitive functions of the brain. The purpose of this study is to assess the relationship between serum BDNF level and cognitive function in middle-aged (40-60years) male chronic smokers. The material used in the study, Brain-derived neurotrophic factor (BDNF) and General Memory Scale (GMS) to assay ELISA, and to test the cognitive function respectively. The results showed that serum BDNF level of chronic smokers (19.19±6.05ng/ml) was comparable with that of non-smokers (20.83±8.63ng/ml). The total GMS scores of chronic smokers (n=41) had significantly lowered total GMS scores (56.88±12.24) than that of non-smokers (n=41) (67.74±7.59) demonstrated cognitive functions. Although the cognitive function of chronic smokers was significantly lower than that of non-smokers, serum BDNF level of chronic smokers was not significantly different from non-smokers (p>0.05). Moreover, serum BDNF level was positively correlated with cognitive function (total GMS scores) in both chronic smokers’ group (r =0.453, p=0.003) and non-smokers group (r =0.458, p=0.003). The study results indicate, even in middle-age healthy adults, chronic smoking would impair cognitive function. The study concludes by portending the role of BDNF in cognitive function, whether or not the individuals are chronic smokers.